2022
DOI: 10.1101/2022.05.18.492177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Coordination Disorder: What Can We Learn From Recombinant Inbred Mice Using Motor Learning Tasks and Quantitative Trait Locus Analysis

Abstract: Developmental Coordination Disorder (DCD) is a motor skills disorder that affects 5-6% of all school-aged children. There is an indication that DCD has an underlying genetic component due to its high heritability. Therefore, we we have explored the use of a recombinant inbred family of mice known as the BXD panel to understand the genetic basis of complex traits (i.e., motor learning) through identification of Quantitative Trait Loci (QTLs). The overall aim of this study was to utilize the QTL approach to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The research results showed reduced gray matter volume related to connections presented in the brainstem. In a measurement made using the motor assessment tool MABC, with tests that activate the specific affected areas of the brainstem, a significant positive correlation was shown in that the reduced volume of the gray matter is also associated with reduced motor skills that explain the motor learning difficulties that are presented 8 .…”
Section: Developmental Motor Coordination Disorder (Dcd) and Neurolog...mentioning
confidence: 99%
“…The research results showed reduced gray matter volume related to connections presented in the brainstem. In a measurement made using the motor assessment tool MABC, with tests that activate the specific affected areas of the brainstem, a significant positive correlation was shown in that the reduced volume of the gray matter is also associated with reduced motor skills that explain the motor learning difficulties that are presented 8 .…”
Section: Developmental Motor Coordination Disorder (Dcd) and Neurolog...mentioning
confidence: 99%